Solvent-free preparation method of breakage-proof and splash-proof fabric composite membrane material for glass mirror surface
By using a powder mixture of EVA resin, rosin and gallic acid as adhesives, combined with the fiber surface treated with ordinary fabrics and silicon coupling reagents, the problem of the complex preparation process of the existing composite film material and the inability to effectively prevent the fragments from falling off after the lens is broken, achieving efficient and environmentally friendly preparation of mirror protective film materials, significantly improving the protective effect and antibacterial properties.
Patent Information
- Application Number
- CN202510176641.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-18
AI Technical Summary
The preparation process of existing composite film materials is complex and requires high temperature curing, resulting in low production efficiency, serious environmental pollution, and it is impossible to effectively prevent the debris from falling off or splashing after the lens is ruptured.
The powder mixture of raw materials such as EVA resin, rosin and gallic acid is used as the adhesive, instead of traditional organic solvent-based adhesives or hot melt adhesives, ordinary fabrics are used as fiber reinforced materials, and the fiber surface is treated with silicon coupling reagents, which significantly improves the strength and antibacterial properties of the composite film. This method does not require high-temperature heating, and can cure quickly at medium temperature, simplify production processes and reduce energy consumption.
The mirror protective film material with high adhesion, shatterproof and splash-proof performance has been achieved, which significantly improves the protection effect of the glass mirror, reduces environmental pollution and health risks, and maintains good antibacterial performance in a warm and humid environment.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a fabric composite film material for protecting glass mirror products, in particular to a fabric composite film material for preventing fragments from falling off and splashing after a lens is broken and a preparation method thereof, which is suitable for enhancing the safety of glass mirrors and belongs to the field of new protective coating materials. Background Art
[0002] As a widely used material, glass plays an important role in many fields such as home furnishing, construction, automobile, and electronics. However, the inherent brittleness of glass makes it easy to break when impacted by external forces, and the fragments may cause harm to the human body or the environment. Therefore, improving the impact resistance and anti-shatter and anti-splash functions of glass has become an important research direction in modern industrial design.
[0003] As the market's requirements for the shatterproof and splashproof performance of glass mirrors are increasing, traditional shatterproof treatment methods such as tempered glass and laminated glass can no longer meet consumer demand. These traditional methods have obvious limitations. For example, although tempered glass has high mechanical strength, it still produces small fragments when it breaks; although laminated glass can prevent fragments from falling off, it is limited in practical applications due to the difficulty of processing and high cost. In order to improve the shatterproof and splashproof performance of glass materials in an economical and convenient way, the patent publication number CN101724340A discloses a production method and application method of a glass shatterproof coating, wherein silicone resin, silicone rubber, butyl acetate, silicone resin curing agent or silicone rubber curing agent are mixed, stirred and ground at room temperature according to weight ratio; filtered to obtain a milky white glass coating; the coating is directly sprayed on the glass, and then dried at a low temperature of 80℃~100℃ and a high temperature of 180℃~220℃. Patent publication number CN217813112U discloses a durable anti-shatter laminated glass, which avoids the phenomenon that the impact force is directly transmitted to the edge of the laminated glass and causes shattering, thereby greatly improving the anti-shatter performance of the laminated glass. Patent publication number CN216675339U discloses a tempered glass anti-shatter protection device, which solves the problem of lack of protection mechanism to protect the tempered glass during the display of the tempered glass in the terminal store. However, these technologies still have problems such as complex process, serious pollution, and poor anti-shatter and anti-splash effect.
[0004] In recent years, more and more researchers have begun to pay attention to the use of composite film materials to protect glass. Composite film materials can not only effectively enhance the surface strength of glass, but also effectively prevent fragments from splashing and falling off when the glass breaks. For example, patent publication number CN118146437A discloses a new impact-resistant buffer material and its preparation method. The new impact-resistant buffer material based on a mixture of a polymer network and an ionic liquid medium is used for glass protection, microelectronic component protection, precision device protection, etc. However, the current anti-shatter and anti-splash technology using composite film materials still faces technical challenges. For example, (1) The preparation process is complex. The existing composite film preparation process mostly uses solvent dissolution or high-temperature heating methods, which requires a long processing time; (2) A high-temperature curing process is required. The preparation of traditional protective film materials requires high-temperature curing and a long processing time, resulting in low production efficiency; (3) Environmental pollution is generated; (4) The protective film cannot effectively prevent fragments from falling off or splashing after the lens breaks. Traditional film materials use organic solvents in the production process, which pollutes the environment. In order to solve the above technical problems, the present invention provides a mirror protective film material with high adhesion, anti-shattering, anti-splashing performance, and low-temperature rapid curing, and reduces production costs, simplifies the production process, and improves the environmental performance of the film by optimizing the formula and processing technology.
[0005] In the actual application of glass mirrors, antibacterial performance is an important technical indicator to meet the needs of specific scenarios. In indoor environments, such as bathrooms and kitchens, the surface of glass mirrors is exposed to high humidity and high temperature conditions for a long time, which is easy to breed bacteria, causing the protective film to deteriorate, produce odors or form stains, affecting its appearance and service life. Therefore, the protective film of the glass mirror also needs to have good antibacterial properties. However, the antibacterial function is not found in the glass mirror protective film materials prepared by the prior art. Summary of the invention
[0006] In view of this, in order to solve the above-mentioned shortcomings existing in the prior art, the present invention provides a method for preparing a mirror-surface anti-shattering and splash-proof fabric composite membrane material with antibacterial function which does not require an organic solvent and does not require high-temperature heating.
[0007] To achieve the above object, the present invention provides the following technical solutions: The present invention adopts a powder mixture of raw materials such as EVA resin, rosin and gallic acid as an adhesive for the composite film material, replacing the traditional organic solvent adhesive or hot melt adhesive, thereby simplifying the production process of the anti-shatter and splash-proof glass mirror. The method avoids the use of organic solvents, not only helps to reduce environmental pollution, but also reduces the potential health risks to on-site operators.
[0008] The present invention uses common fabrics such as polyester, cotton and polyester-cotton blended fabrics as fiber reinforcement materials for the composite film, which can significantly improve the anti-shatter and anti-splash performance of the glass mirror. Compared with the protective film prepared using only polymer adhesive, when using fabric reinforcement materials, only a small amount of adhesive is required to achieve a more excellent protective effect.
[0009] For hydrophobic fiber materials such as polyester fabrics and polyester-cotton blended fabrics, the present invention uses a silicon coupling agent to treat the fiber surface to enhance its surface polarity and water absorption properties, making it similar to the properties of cotton fabrics. This method can significantly improve the interfacial compatibility between fabric fibers and adhesives, thereby effectively improving the strength of the composite film.
[0010] The present invention crushes raw materials such as EVA resin, rosin, gallic acid, etc. into fine powders with an average mesh size of 100 to 120. Powders with smaller particle sizes are helpful for uniform mixing of various raw materials, achieving better compatibility in the composite film forming process, and enabling the composite film to achieve a better bonding effect.
[0011] In view of the surface characteristics of the back side of the glass mirror, the present invention preferably uses EVA, which not only ensures good mechanical strength, flexibility and elasticity of the composite film, but also ensures sufficient adhesion to the mirror surface and fabric fibers.
[0012] The present invention selects water-based rosin as a tackifier and selects a rosin variety with an appropriate softening point to ensure that it can match the preferred EVA variety, exert an excellent tackifying effect, effectively reduce the production temperature, shorten the heating time, and reduce energy consumption.
[0013] The present invention selects gallic acid as the main antibacterial component, which effectively inhibits the reproduction of microorganisms in a humid environment and ensures the long-term stable use of the composite membrane material in a warm and humid environment.
[0014] Preferably, the method for preparing the anti-shatter and splash-proof fabric composite membrane material comprises the following steps: Grind EVA resin, rosin, gallic acid and other raw materials into powder of appropriate mesh size; Use a V-shaped powder mixer to mix the above raw material powders in appropriate proportions; Use fabric surface finishing agents to treat the surface of fabric fibers and regulate the polarity and moisture of the fiber surface; Use a powder spray device to disperse the above powder mixture in appropriate amounts on the fabric and the back of the glass mirror; At a medium temperature of 60℃ to 80℃, the fabric and the mirror are pressed together to complete the composite film forming preparation and achieve the anti-shatter and splash-proof functions.
[0015] Preferably, the vinyl acetate (VA) content in the EVA resin is in the range of 20% to 30%.
[0016] Preferably, the rosin is water-based rosin, and its softening point ranges from 80°C to 90°C.
[0017] Preferably, the powder has an appropriate mesh size of 100 to 120 meshes.
[0018] Preferably, the ratio of EVA to rosin is in the range of 3:1 to 1:1, and the optimal ratio is 2:1.
[0019] Preferably, the fabric surface finishing method for adjusting the surface polarity of polyester fabric comprises the following steps: First, a 1% mass concentration silane coupling agent (KH-550) solution was used to immerse the polyester fabric at 50°C to 60°C for 30 minutes to 60 minutes.
[0020] Secondly, air-dry the fabric at 110°C to 120°C for 30 to 60 minutes to ensure that the surface of the polyester fabric reacts with the silane coupling agent to enhance the adhesion between the film and the substrate.
[0021] The improvements and principles of the present invention are as follows: The present invention adopts the powder mixture as the adhesive of the composite membrane material, avoids the use of organic solvents (such as acetone), reduces environmental pollution, and reduces the potential risk to the health of on-site operators.
[0022] The present invention selects common fabric as the fiber reinforcement material, which significantly improves the protective effect on the glass mirror surface.
[0023] The present invention preferably uses fine powder raw materials, which helps to evenly mix various raw materials and achieve better composite effects.
[0024] In view of the surface characteristics of the back side of the glass mirror, the present invention prefers EVA type, preferably tackifier type, and preferably mixed powder component ratio, which significantly improves the composite flexibility and elasticity and ensures that the composite interface has sufficient adhesion.
[0025] The present invention can complete the composite film forming process at a medium temperature of 60° C. to 80° C. in a relatively short time of less than 1 minute, thereby simplifying the production process, reducing energy consumption and improving production efficiency.
[0026] The composite film product of the present invention can generate a strong bonding force of not less than 3N / cm. After a 500-gram stainless steel ball falls freely from a height of 1 meter and causes the mirror surface to break, no fragments with a diameter greater than 1 centimeter fall off, and the amount of glass fragments separated from the matrix is not higher than 2% of the mass of the glass mirror body. The antibacterial rate of the composite film against Escherichia coli and Staphylococcus aureus is not less than 95%.
[0027] In summary, the beneficial effects of the present invention are as follows: (1) simple process and high production efficiency; (2) solvent-free preparation, which reduces the impact on the environment and health; (3) medium temperature and short time curing, which can be completed by heating at 80°C for 30 seconds, which significantly improves production efficiency; (4) antibacterial and antibacterial, improving the durability of the membrane material; (5) the anti-shatter and anti-splash effect is significantly better than the existing technology.
[0028] In the present invention, the preferred vinyl acetate content in the EVA resin has an important influence on the flexibility and adhesion of the composite film. If the vinyl acetate content is too low, the adhesive force of the film to the polar interface is insufficient; if the vinyl acetate content is too high, the mechanical strength of the film is weakened. In view of the surface characteristics of the back side of the glass mirror, the present invention preferably selects EVA types, and selects EVA varieties with a vinyl acetate content ranging from 20% to 30%, to ensure that the composite film has good mechanical strength, flexibility, and bonding strength to the fabric and the mirror surface.
[0029] The present invention adopts water-based rosin as a tackifier and selects a rosin variety with a softening point range of 80° C. to 90° C., which can be benignly compatible with the preferred EVA, achieve a more excellent tackifying effect, and can significantly reduce the production temperature, shorten the heating time, and reduce energy consumption.
[0030] The average mesh number parameters of rosin and EVA powder in the mixed powder directly affect the film-forming properties of the composite film. Too large a particle size may result in an uneven film surface and affect the adhesion between the film and the substrate; too small a particle size may affect the anti-shattering effect. The present invention selects a powder mixing mesh number of 100 to 120, which has been experimentally verified to form a smooth film with strong adhesion.
[0031] The present invention selects gallic acid as the main antibacterial component. Gallic acid can be mixed with main powders such as EVA and rosin, and has good compatibility after heating and melting, and can give the composite film an excellent antibacterial effect.
[0032] The present invention uses a combination of EVA resin and rosin powder, and after optimizing the ratio and particle size, it can be cured in a short time (30 seconds) under medium temperature conditions (below 80°C). The on-site preparation production process is simple, high-temperature heating can be avoided, energy consumption is saved, and production efficiency is improved. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is clearly described in detail below in conjunction with specific embodiments.
[0034] Example 1
[0035] First, soak the polyester cloth in a 0.5% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 90°C) powder and EVA (VA content 20%) powder through a 100-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:2, add 1wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 1.5±0.3g / cm 2 Then, pressure was applied at 80°C for 20 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0036] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 5.4N / cm, and the longitudinal peeling force between the mirror and the fabric is 5.8N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 0.9%. The composite film has an antibacterial rate of 99% against Escherichia coli and 99% against Staphylococcus aureus.
[0037] Example 2
[0038] First, soak the polyester cloth in a 2% concentration of fumed silica dispersion, adjust the pH to 4-6, treat at 90°C for 15 minutes, and air-dry at 120°C for 30 minutes. Next, sift the rosin (softening point 80°C) powder and EVA (VA content 30%) powder through a 120-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:2, add 0.5wt% gallic acid (based on EVA mass), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the colloid dosage is controlled to 1.8±0.3g / cm 2 Then, pressure was applied at 70°C for 25 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0039] The test results of product performance are as follows: the transverse peeling force between the mirror and the fabric is 5.0N / cm, and the longitudinal peeling force between the mirror and the fabric is 4.9N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1cm fall off, and the mass ratio of the detached fragments is 1.0%. The composite film has an antibacterial rate of 96% against Escherichia coli and 97% against Staphylococcus aureus.
[0040] Example 3
[0041] First, soak the polyester cloth in a 0.5% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 80°C) powder and EVA (VA content 20%) powder through a 100-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:2, add 1wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 1.5±0.3g / cm 2 Then, pressure was applied at 80°C for 20 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0042] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 5.7N / cm, and the longitudinal peeling force between the mirror and the fabric is 6.0N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 0.8%. The composite film has an antibacterial rate of 99% against Escherichia coli and 99% against Staphylococcus aureus.
[0043] Example 4
[0044] First, soak the polyester cloth in a 0.8% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, screen the rosin (softening point 90°C) powder and EVA (VA content 30%) powder through a 120-mesh sieve, mix the screened rosin and EVA in a mass ratio of 1:2, add 1wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 1.5±0.3g / cm 2 Then, pressure was applied at 80°C for 25 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0045] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 6.0N / cm, and the longitudinal peeling force between the mirror and the fabric is 6.4N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 0.6%. The composite film has an antibacterial rate of 99% against Escherichia coli and 99% against Staphylococcus aureus.
[0046] Example 5
[0047] First, soak the polyester cloth in a 0.8% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 80°C) powder and EVA (VA content 20%) powder through a 100-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:2, add 1wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 1.5±0.3g / cm 2 Then, pressure was applied at 80°C for 20 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0048] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 5.8N / cm, and the longitudinal peeling force between the mirror and the fabric is 6.0N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1cm fall off, and the mass ratio of the detached debris is 0.7%. The composite film has an antibacterial rate of 96% against Escherichia coli and 96% against Staphylococcus aureus.
[0049] Example 6
[0050] First, soak the polyester cloth in a 0.5% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 90°C) powder and EVA (VA content 30%) powder through a 120-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:2, add 0.5wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 1.5±0.3g / cm 2 Then, pressure was applied at 70°C for 30 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0051] The test results of product performance are as follows: the transverse peeling force between the mirror and the fabric is 6.1N / cm, and the longitudinal peeling force between the mirror and the fabric is 6.4N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1cm fall off, and the mass ratio of the detached fragments is 0.4%. The composite film has an antibacterial rate of 95% against Escherichia coli and 95% against Staphylococcus aureus.
[0052] Example 7
[0053] First, soak the polyester cloth in a 0.8% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 90°C) powder and EVA (VA content 20%) powder through a 100-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:2, add 1wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 2.0±0.3g / cm 2 Then, pressure was applied at 60°C for 30 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0054] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 4.9N / cm, and the longitudinal peeling force between the mirror and the fabric is 4.6N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 1.1%. The composite film has an antibacterial rate of 96% against Escherichia coli and 97% against Staphylococcus aureus.
[0055] Example 8
[0056] The rosin (softening point 80℃) powder and EVA (VA content 20%) powder were screened through a 100-mesh sieve. The screened rosin and EVA were mixed at a mass ratio of 1:2. 1wt% gallic acid (based on the mass of EVA) was added and stirred evenly using a powder homogenizer to ensure that the three materials were fully mixed. The mixed powder was evenly coated on the surface of the pure cotton fabric, and the amount of colloid was controlled to 1.0±0.3g / cm 2 Then, pressure was applied at 80°C for 20 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0057] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 4.5N / cm, and the longitudinal peeling force between the mirror and the fabric is 4.7N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 1.2%. The composite film has an antibacterial rate of 97% against Escherichia coli and 95% against Staphylococcus aureus.
[0058] Example 9
[0059] First, soak the polyester-cotton fabric in a 1% silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 90°C) powder and EVA (VA content 20%) powder through a 120-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:2, add 1wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 1.5±0.3g / cm 2 Then, pressure was applied at 80°C for 20 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0060] The test results of product performance are as follows: the transverse peeling force between the mirror and the fabric is 4.9N / cm, and the longitudinal peeling force between the mirror and the fabric is 4.8N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1cm fall off, and the mass ratio of the detached fragments is 1.1%. The composite film has an antibacterial rate of 95% against Escherichia coli and 96% against Staphylococcus aureus.
[0061] Example 10
[0062] The rosin (softening point 80℃) powder and EVA (VA content 30%) powder were screened through a 120-mesh sieve, and the screened rosin and EVA were mixed at a mass ratio of 1:2. 0.5wt% gallic acid (based on the mass of EVA) was added, and the powder was evenly stirred using a powder homogenizer to ensure that the three materials were fully mixed. The mixed powder was evenly coated on the surface of the pure cotton fabric, and the amount of colloid was controlled to 1.5±0.3g / cm 2 Then, pressure was applied at 70°C for 30 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0063] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 5.2N / cm, and the longitudinal peeling force between the mirror and the fabric is 5.4N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 0.8%. The composite film has an antibacterial rate of 95% against Escherichia coli and 96% against Staphylococcus aureus.
[0064] Embodiment 11
[0065] First, soak the polyester-cotton fabric in a 0.5% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 90°C) powder and EVA (VA content 30%) powder through a 100-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:2, add 0.5wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 1.5±0.3g / cm 2 Then, pressure was applied at 70°C for 30 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0066] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 5.6N / cm, and the longitudinal peeling force between the mirror and the fabric is 5.1N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached fragments is 0.6%. The composite film has an antibacterial rate of 96% against Escherichia coli and 97% against Staphylococcus aureus.
[0067] Comparative Example 12 First, the polyester cloth was soaked in a 1% silane coupling agent (KH-550) solution and treated at 60°C for 45 minutes; then air-dried at 110°C for 60 minutes. Next, rosin (softening point 120°C) powder and EVA (VA content 10%) powder were screened through an 80-mesh sieve. The screened rosin and EVA were mixed in a mass ratio of 1:1, 0.5wt% gallic acid (based on the mass of EVA) was added, and a powder homogenizer was used to stir evenly to ensure that the three materials were fully mixed. The mixed powder was evenly coated on the surface of the polyester cloth, and the colloid dosage was controlled to 2.0±0.3g / cm 2 Then, pressure was applied at 70°C for 30 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0068] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 2.5N / cm, and the longitudinal peeling force between the mirror and the fabric is 3.0N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror is broken, no fragments with a diameter greater than 1cm fall off, and the mass ratio of the detached debris is 1.8%. The composite film has an antibacterial rate of 95% against Escherichia coli and 96% against Staphylococcus aureus.
[0069] Comparative Example 13 First, soak the polyester cloth in a 1% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 100°C) powder and EVA (VA content 40%) powder through a 150-mesh sieve, mix the sifted rosin and EVA in a mass ratio of 1:3, add 1wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. Adjust the particle size of rosin and EVA powder (120µm) and sieve. Evenly coat the mixed powder on the surface of the polyester cloth, and control the amount of colloid to 1.0±0.3g / cm 2 Then, pressure was applied at 60°C for 20 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0070] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 3.2N / cm, and the longitudinal peeling force between the mirror and the fabric is 3.4N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 1.6%. The composite film has an antibacterial rate of 99% against Escherichia coli and 99% against Staphylococcus aureus.
[0071] Comparative Example 14 First, soak the polyester cloth in a 0.8% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, screen the rosin (softening point 80°C) powder and EVA (VA content 10%) powder through a 120-mesh sieve, mix the screened rosin and EVA in a mass ratio of 1:1, add 0.5wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 2.0±0.3g / cm 2Then, pressure was applied at 70°C for 20 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0072] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 2.4N / cm, and the longitudinal peeling force between the mirror and the fabric is 2.7N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 1.9%. The composite film has an antibacterial rate of 95% against Escherichia coli and 95% against Staphylococcus aureus.
[0073] Comparative Example 15 First, soak the polyester cloth in a 1% silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 100°C) powder and EVA (VA content 40%) powder through a 150-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:1, add 0.5wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 2.0±0.3g / cm 2 Then, pressure was applied at 70°C for 20 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0074] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 3.6N / cm, and the longitudinal peeling force between the mirror and the fabric is 3.8N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface breaks, no fragments with a diameter greater than 1cm fall off, and the mass ratio of the detached debris is 1.4%. The composite film has an antibacterial rate of 96% against Escherichia coli and 95% against Staphylococcus aureus.
[0075] Comparative Example 16 First, soak the polyester cloth in a 0.5% concentration of silane coupling agent (KH-550) solution and treat it at 60°C for 45 minutes; then air-dry it at 110°C for 60 minutes. Next, sift the rosin (softening point 100°C) powder and EVA (VA content 10%) powder through a 150-mesh sieve, mix the sifted rosin and EVA at a mass ratio of 1:1, add 0.5wt% gallic acid (based on the mass of EVA), and use a powder homogenizer to stir evenly to ensure that the three materials are fully mixed. The mixed powder is evenly coated on the surface of the polyester cloth, and the amount of colloid is controlled to 1.0±0.3g / cm 2Then, pressure was applied at 60°C for 30 seconds by a hot press to ensure that the composite film was flat and tightly bonded to the substrate. After curing, the adhesion, anti-shatter and anti-splash effect, and antibacterial properties of the composite film material were measured.
[0076] The product performance test results are characterized by: the transverse peeling force between the mirror and the fabric is 3.9N / cm, and the longitudinal peeling force between the mirror and the fabric is 3.4N / cm. A 500g stainless steel ball is dropped freely from a height of 1 meter. After the mirror surface is broken, no fragments with a diameter greater than 1 cm fall off, and the mass ratio of the detached debris is 1.6%. The composite film has an antibacterial rate of 95% against Escherichia coli and 95% against Staphylococcus aureus.
[0077] The above embodiments and comparative examples are summarized as follows:
[0078] Table 1. Mirror-surface anti-shatter and splash-proof fabric composite membrane materials and their preparation conditions.
[0079]
[0080] Table 2. Product performance characterization results.
Claims
1. A solvent-free preparation method of a glass mirror anti-shatter and splash-proof fabric composite membrane material, characterized in that: The steps include: (1) Grinding EVA resin and rosin into powders with an average particle size, and mixing them with gallic acid in a certain proportion to form a powder mixture; (2) dispersing the powder mixture on the surface of the fabric; (3) Pressing the fabric and the glass mirror at a medium temperature of 60°C to 80°C to complete the preparation of the composite film.
2. The method for preparing the glass mirror anti-shattering and splash-proof fabric composite membrane material according to claim 1, characterized in that: The molar content of the vinyl acetate structural unit in the EVA resin is 20% to 30%.
3. The method for preparing the glass mirror anti-shattering and splash-proof fabric composite membrane material according to claim 1, characterized in that: The rosin is water-based rosin, and its softening point ranges from 80°C to 90°C.
4. The method for preparing the glass mirror anti-shattering and splash-proof fabric composite membrane material according to claim 1, characterized in that: The average powder mesh number of the powder is 100 mesh to 120 mesh.
5. The method for preparing the glass mirror anti-shattering and splash-proof fabric composite membrane material according to claim 1, characterized in that: The proportion of raw material components is calculated based on the mass of EVA being 100, the mass range of rosin is 33~100, and the mass range of gallic acid is 0.5~1.
6. The method for preparing the glass mirror anti-shattering and splash-proof fabric composite membrane material according to claim 1, characterized in that: The fabric is cotton fabric, polyester-cotton blended fabric, or polyester fabric.
7. The method for preparing the glass mirror anti-shattering and splash-proof fabric composite membrane material according to claim 1, characterized in that: The fabric is a polyester fabric pretreated with a silicon coupling agent, and the fabric surface finishing method comprises the following steps: first, using an ethanol solution of a silane coupling agent with a mass concentration of 1%, immersing the polyester fabric at 50° C. to 60° C. for 30 minutes to 60 minutes; second, air-drying the fabric at 110° C. to 120° C. for 30 minutes to 60 minutes.
8. The method for preparing the glass mirror anti-shattering and splash-proof fabric composite membrane material according to claim 1, characterized in that: The powder mixture is used in an amount of 1.5 to 2.0 g / cm 2 .
9. The method for preparing the glass mirror anti-shattering and splash-proof fabric composite membrane material according to claim 1, characterized in that: The pressing time is 20 to 30 seconds.
Citation Information
Patent Citations
Method for producing anti-shatter coating for glass and application method thereof
CN101724340A
Novel impact-resistant buffer material as well as preparation method and application thereof
CN118146437A
Toughened glass breakage-proof protection device
CN216675339U
Anti-fragmentation durable laminated glass
CN217813112U
Impact absorption sheet for flat panel display, process for producing the same, and flat panel display
CN101156193A